1999
DOI: 10.1111/j.1572-0241.1999.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the Esophagus and Barrett's Esophagus: A Population-Based Study

Abstract: The rate of esophageal adenocarcinoma in Denmark has increased eightfold over a 20-yr period, and this increase is not explained by changes in classification or diagnostic routines. More than 98% of esophageal adenocarcinomas were found in patients who could not have entered endoscopic surveillance, as Barrett's esophagus had not been diagnosed before the cancer diagnosis. Endoscopic surveillance to detect dysplasia may be an option for the individual patient with Barrett's esophagus, but these screening progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(69 citation statements)
references
References 24 publications
3
64
0
2
Order By: Relevance
“…An answer to this intriguing finding remains unclear. We speculate that because patients with high BMI are diagnosed with GERD more often than those with low BMI, [19][20][21][22][23] patients with high BMI are more likely to undergo endoscopic surveillance and this could result in the diagnosis of early EC. Lagergren et al 11 reported an odds ratio of 7.7 for EAC among patients with GERD symptoms compared with individuals without GERD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…An answer to this intriguing finding remains unclear. We speculate that because patients with high BMI are diagnosed with GERD more often than those with low BMI, [19][20][21][22][23] patients with high BMI are more likely to undergo endoscopic surveillance and this could result in the diagnosis of early EC. Lagergren et al 11 reported an odds ratio of 7.7 for EAC among patients with GERD symptoms compared with individuals without GERD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…4 The incidence of these 2 types of cancers has progressively risen in the Western world. 2,[5][6][7][8] However, at the present time, it is impossible to predict which patients are at risk of neoplastic progression and all patients are advised to undergo a regular endoscopic followup. 9,10 BE patients have a 30 -125-fold increased risk of developing esophageal AC compared to the general population.…”
mentioning
confidence: 99%
“…In a population-based study reported by Bytzer et al (1999), more than 98% of esophageal adenocarcinoma was detected in patients with previously undiagnosed Barrett's esophagus. It has been postulated that intensive long-term treatment of GERD by anti-reflux therapies in patients with Barrett's esophagus may lower the incidence of esophageal adenocarcinoma (Hillman, 2004;Cooper, 2006;Nguyen et al, 2009).…”
Section: Barrett's Esophagus and β-Carotene Therapy: Symptomatic Imprmentioning
confidence: 96%